Who is who in thermal analysis and calorimetry - Liptay, Gyorgy; Szilagyi, Imre Miklos (Hot Topics in Thermal Analysis and Calorimetry, 2014)
This is an expanded and revised second edition,  presenting accurate and comprehensive information about our leading thermal scientists to current and future generations. In our globalized world, most researchers in thermal analysis do not know each other in person and are not familiar with each other's achievements. This volume provides the reader with an up-to-date list of the prominent members in this community. The publication contains only living scientists. The selection is based partly on several decades of the editors' personal professional experience and also partly on the opinion of the Regional Editors of the Journal of Thermal Analysis and Calorimetry.